2000
DOI: 10.1001/archpsyc.57.6.572
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Suppression by Light in Euthymic Bipolar and Unipolar Patients

Abstract: The general hypothesis of increased light sensitivity in bipolar patients was not supported. However, melatonin secretion abnormalities were confirmed in the subgroup with bipolar I disorder. Further assessments of circadian rhythm disruption as a vulnerability marker in bipolar illness are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
138
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 44 publications
9
138
1
3
Order By: Relevance
“…In this respect, valproate and lithium share a common biological effect as we have previously reported similar effects in volunteers taking lithium (Hallam et al, 2004). Both sets of data are in accord with a trend noted in bipolar patients by Nurnberger et al (2000). They showed that in drug-free bipolar patients, the effect of light on nocturnal melatonin secretion was greater than that in patients treated with lithium.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this respect, valproate and lithium share a common biological effect as we have previously reported similar effects in volunteers taking lithium (Hallam et al, 2004). Both sets of data are in accord with a trend noted in bipolar patients by Nurnberger et al (2000). They showed that in drug-free bipolar patients, the effect of light on nocturnal melatonin secretion was greater than that in patients treated with lithium.…”
Section: Discussionsupporting
confidence: 87%
“…Several questions remain concerning sensitivity, specificity, and the effects of medication on responses observed in patients before melatonin light sensitivity can be accepted as an endophenotype. Indeed, some suggestion of the effect of medication on nocturnal melatonin light sensitivity was evident in at least one report (Nurnberger et al, 2000). Among bipolar I patients, the greatest melatonin sensitivity was observed in those free of medication for at least 5 weeks, while those taking lithium alone had melatonin suppression similar to that of controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those patients particularly vulnerable to environmental influences, alterations to the combinations or dose of medications may be particularly useful. Previous studies indicate that some medications such as lithium and valproate (mood stabilizers) have chronobiotic activity (ie assist in normalizing circadian rhythms) (9,55,56). Recent evidence indicates that this chronobiotic effect may be mediated through intracellular glucogen synthase kinase (GSK) 3b and clock gene activation (37,(57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to environmental changes is best seen in patients with seasonal affective disorder, which responds to bright light therapy, who experience marked depression in winter months (4)(5)(6)(7)(8). In a similar manner, researchers have shown abnormalities in hormonal responsiveness (ie melatonin) to bright light in patients with BPAD (9)(10)(11)(12). In patients with bipolar disorder, changes in levels of melatonin are proposed to cause disturbances in the circadian rhythm because it is the primary regulator of the intrinsic circadian pacemakers (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 91%